STRATEGI MENGEMBANGKAN INISIATIF DAN PARTISIPASIMASYARAKAT LOKAL UNTUK MENGEMBANGKAN WISATA PERDESAAN BAGI PENINGKATAN KESEJAHTERAAN MASYARAKAT - Musthofa, Budiman Mahmud (UI Scholars Hub, 2019)
Rural tourism is one of the opportunities for rural development in Indonesia and also for the development of national tourism. Rural tourism contributes greatly to the government and society in developing the national tourism sector to improve welfare while preserving the cultural values of the community. There are many facts in the field that show the success and failure of the development of a tourist village, one of the problem lies in the involvement and support of the community. This study wants to explain more deeply how rural tourism gained community support from the planning stage to its implementation. This study was conducted with a qualitative approach through observation data collection techniques and in-depth interviews to reveal data in more detail. The results of the study indicate that community participation is the key that must be done for the success of rural tourism development in Indonesia. Local initiatives need to be raised and promoted along with strengthening local champions who will later become agents of community change. At the same time a network between stakeholders involved in the development of rural tourism needs to be developed so as to accelerate the self mobilization. Theoretically this study enriches research in the fields of tourism, empowerment and social welfare.